Socioeconomic differences in metabolic syndrome development and the role of perceived stress. (20th October 2021) - Hoveling, LA; Liefbroer, AC; Bültmann, U; Smidt, N
Abstract: Background: Metabolic syndrome (MetS) incidence strongly varies by socioeconomic position (SEP), but to date, no studies have assessed the mediating role of perceived stress from long-term difficulties (chronic stress) in this association. This study examines the mediating role of chronic stress in the associations between SEP measures education, occupational prestige and income, and incident MetS and whether the associations between chronic stress and MetS are moderated by sex. Methods: An adult subsample (n = 53, 216) of the Lifelines Cohort Study without MetS at baseline was used. MetS incidence was measured at follow-up (median follow-up time 3.9 years) defined according to the NCEP-ATPIII criteria. Chronic stress was measured with the Long-term Difficulties Inventory (LDI) and consists of 12 items evaluating (on a 3-point Likert scale) to what extent various domains of life had been perceived as stressful during the last year. Direct associations between SEP, chronic stress and incident MetS were estimated using multivariable logistic and linear regression analyses, adjusted for age, sex, the other SEP measures and follow-up time. The mediating percentages of chronic stress explaining the associations between SEP and incident MetS were estimated using the Karlson-Holm-Breen method. Results: At follow-up 7.4% of the participants developed MetS. Years of education and occupational prestige were inversely associated with MetS incidence. Chronic stress suppressed the association between education and MetS incidence (5.4%) as well as the association between occupational prestige and MetS incidence (6.0%). No effect modification of sex in the chronic stress-MetS pathway was observed. Conclusions: Chronic stress does not explain educational and occupational differences in developing MetS. In fact, individuals with more years of education or a higher occupational prestige perceive more chronic stress, compared to their lower SEP counterparts. Key messages: Education and occupational prestige are inversely associated with metabolic syndrome incidence. Chronic stress does not explain SEP differences in developing metabolic syndrome.